Iowa RBA, August 18, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for August 18, 1997. Highlights of the update include sightings of a Roseate Spoonbill, Snowy Egret, an Ibis species, and a Pacific Loon. Also of note was the large number of shorebirds passing through the state and the beginning of the Passerine movement. Also included are handwritten notes for the next week's update with sightings of a Red-necked Phalarope, Sandhill Cranes, Olive-sided Flycatcher, and a Pine Warbler. Epson - sheet feed/flatbed